A Structural Move Analysis of Abstracts in Undergraduate Theses: A Case Study at Universitas Kristen Indonesia - Male, H (KnE Social Sciences, 2018)
Writing the abstract of a final project or undergraduate thesis can be difficult for undergraduate students due to the lack of awareness of writing in academic genres, particularly the moving structure of each section of a research work. To overcome this issue, the writer attempts to analyze the rhetorical structure of undergraduate students’ research papers in the abstract section. The aim of the research is to find out the rhetorical moves in the abstract section and whether or not this study was similar to the study by Bhatia [1]. To analyze the data, the writer followed Bhatia’s move analysis [1]. The results found that the majority of English as a Foreign Language (EFL) students’ abstracts confirmed Bhatia’s findings. It is highly recommended that faculties and/or teachers should provide fixed structural move guidelines to assist students in writing their final project. Keywords: rhetorical steps or moves, undergraduate theses